(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Ovarian cancer is one of the most common causes of gynecologic neoplasm all over the world. Objective:The objective is to shed light on the role of p53 protein and patient`s age in the pathogenesis of ovarian lesions. Methods:Paraffin embedded blocks of 62 patients with ovarian lesions were studied. Thirty-five cases of surface epithelial ovarian tumors, (31 cases of invasive surface epithelial ovarian tumors, and 4 cases of borderline intermediate malignancy cases of neoplastic ovarian cystic lesions). In addition, eighteen cases of benign neoplastic ovarian cystic lesions and 9 cases of non- neoplastic functional one were enrolled in this study. All of cases included, were stained with p53 by immunohistochemistry. Results: Immunohistochemistry for p53 showed that malignant cases were positive for p53 while all benign cases were negative for p53 and the borderline cases were also negative for p53. The non-neoplastic cases were negative for p53. There is a significant statistical difference in P53 expression in malignant cases compared to other groups (P < 0.001). A significant difference in mean age of malignant and border line cases in comparison with benign and non-neoplastic cases; (P < 0.001). Conclusion:Protein p53 may play a role in the pathogenesis of malignant ovarian cancer but not in benign lesions. The age of the patient has a role as a risk factor in ovarian lesions. Keywords:Ovarian lesion, ovarian cancer, p53, immunohistochemistry.